Developmental Evolution of Hypaxial Muscles: Insights From Cyclostomes and Chondrichthyans - Kusakabe, Rie; Tanaka, Masako; Kuratani, Shigeru (Frontiers in Cell and Developmental Biology, 2021)
Jawed vertebrates possess two distinct groups of muscles in the trunk (epaxial and hypaxial muscles) primarily defined by the pattern of motor innervation from the spinal cord. Of these, the hypaxial group includes muscles with highly differentiated morphology and function, such as the muscles associated with paired limbs, shoulder girdles and tongue/infrahyoid (hypobranchial) muscles. Here we summarize the latest findings on the evolutionary mechanisms underlying the morphological variety of hypaxial musculature, with special reference to the molecular insights obtained from several living species that diverged early in vertebrate evolution. Lampreys, extant jawless vertebrates, lack many of derived traits characteristic of the gnathostomes, such as jaws, paired fins and epaxial/hypaxial distinction of the trunk skeletal musculatures. However, these animals possess the primitive form of the hypobranchial muscle. Of the gnathostomes, the elasmobranchs exhibit developmental mode of hypaxial muscles that is not identical to that of other gnathostomes in that the muscle primordia relocate as coherent cell aggregates. Comparison of expression of developmental genes, including Lbx genes, has delineated the temporal order of differentiation of various skeletal muscles, such as the hypobranchial, posterior pharyngeal and cucullaris (trapezius) muscles. We have proposed that the sequential addition of distal muscles, associated with expression of duplicated Lbx genes, promoted the elaboration of skeletal musculature. These analyses have revealed the framework of an evolutionary pathway that gave rise to the morphological complexity and diversity of vertebrate body patterns.